Causes of delay in completing assignment at UiTM Pasir Gudang - Mohammad Damanhuri, Muhammad Azamuddin; Badrul Hisham, Siti Noor Aishah; Mohd Rahim, Mohamad Hazim; Nik Saberi, Nik Muhd Harith Irfan; Alimon, Nur Idayu (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2023)
Students at University Teknologi Mara (UiTM) appear to be particularly skilled at putting things off. The objectives of this study are to identify the symptoms and indications of procrastination and to understand why a person procrastinate. We suggest that procrastination may be described as a logical behaviour within a rational choice framework, even though it can occasionally be inefficient. To support our claim, we use survey data acquired from a broad cross-section of students and faculty members. We can forecast who procrastinates, under what conditions they procrastinate. The sample size of this study is 75. Based on our survey, 76% of our respondent admit procrastinating while another 24% not procrastinate the assignment. Large percentages of those surveyed stated that as a result, the quality of their written work, including as papers and projects, as well as their exam results, and, to a lesser extent, whether they were late with their assignments.